Small molecule IVQ, as a prodrug of gluconeogenesis inhibitor QVO, efficiently ameliorates glucose homeostasis in type 2 diabetic mice - Zhou Ting-ting; Zhao Tong; Ma Fei; Zhang Yi-nan; Jiang Jing; Ruan Yuan; Yan Qiu-ying; Wang Gai-hong; Ren Jin; Guan Xiao-wei; Guo Jun; Zhao Yong-hua; et al. (Acta Pharmacologica Sinica, 2019)
Gluconeogenesis is a major source of hyperglycemia in patients with type 2 diabetes mellitus (T2DM), thus targeting gluconeogenesis to suppress glucose production is a promising strategy for anti-T2DM drug discovery. In our preliminary in vitro studies, we found that a small-molecule (E)-3-(2-(quinoline-4-yl)vinyl)-1H-indol-6-ol (QVO) inhibited the hepatic glucose production (HGP) in primary hepatocytes. We further revealed that QVO suppressed hepatic gluconeogenesis involving calmodulin-dependent protein kinase kinase β- and liver kinase B1-adenosine monophosphate-activated protein kinase (AMPK) pathways as well as AMPKindependent mitochondrial function-related signaling pathway. To evaluate QVO’s anti-T2DM activity in vivo, which was impeded by the complicated synthesis route of QVO with a low yield, we designed and synthesized 4-[2-(1H-indol-3-yl)vinyl]quinoline (IVQ) as a prodrug with easier synthesis route and higher yield. IVQ did not inhibit the HGP in primary hepatocytes in vitro. Pharmacokinetic studies demonstrated that IVQ was quickly converted to QVO in mice and rats following administration. In both db/db and ob/ob mice, oral administration of IVQ hydrochloride (IVQ-HCl) (23 and 46 mg/kg every day, for 5 weeks) ameliorated hyperglycemia, and suppressed hepatic gluconeogenesis and activated AMPK signaling pathway in the liver tissues. Furthermore, IVQ caused neither cardiovascular system dysfunction nor genotoxicity. The good druggability of IVQ has highlighted its potential in the treatment of T2DM and the prodrug design for anti-T2DM drug development.